Epidemiological Characteristics and Clinical Outcomes of Coronavirus Disease Patients in Northwest China: High-Volume Research From Low Population Density Regions - Zhu, Jianfei; Zhang, Qingqing; Jia, Chenghui; Wang, Wuping; Chen, Jiakuan; Xia, Yanmin; Wang, Wenchen; Wang, Xuejiao; Wen, Miaomiao; Wang, Hongtao; Zhang, Zhipei; Xu, Shuonan; et al. (Frontiers in Medicine, 2020)
Abstract： Background: The study about transmission characteristics of coronavirus infected disease 2019 (COVID-19) in low density population areas was limited. So we designed this study to analyze the epidemiological characteristics and clinical outcomes of COVID-19 patients in Northwestern China with low density population. Methods: From January 21st to March 11th 2020, all patients diagnosed with novel coronavirus pneumonia (NCP) in Northwestern China with a lower population density were retrospectively analyzed. Categorical variables were summarized as numbers and percentages,the ration between the resident patient (no history of going out during the epidemic) and imported patients can represent the contagious of COVID-19 virus. Hospitalization time was was analyzed as well. Results: A total of 617 COVID-19 patients were reported in Northwestern China, the morbidity and mortality were 0.000005 and 0.011, respectively, further analysis showed that the morbidity was inversely proportional to population density and distance from Wuhan City. In this study, 473 confirmed cases were enrolled to be analyzed, for these patients, 248 patients were residents and 225 patients were imported cases, the ration between them was 1.1. The oldest patient was 94 years, the youngest was only one year old, the median age of the patients was 42 years, 15 patients were child or infant (3.2%), we also found that two patients were pregnant, and one patient give birth to a healthy baby with negative result during her disease course. Interesting, about 17.3% of patients (82 cases) were healthy carriers, without any symptoms during their disease course. One male patient (0.2%) had recurrence of positive test four days after discharge. The median hospitalization time was 16.0 days,rang from 2.0 days to 43.0 days. Further analysis showed that the following variables were correlated significantly with hospitalization time: age (P=0.03) and severity status (P<0.001). Conclusions: Both morbidity and mortality rate of COVID-19 patients in the low density population region were lower than that of the national average of China. All population were susceptible to catch COVID-19 virus. Asymptomatic patients whose positive results should be taken seriously and the hospitalization time of patients were associated with their age and severity status.